Neoadjuvant dabrafenib combined with trametinib for resectable, stage IIIB–C, BRAFV600 mutation-positive melanoma (NeoCombi): a single-arm, open-label, single-centre, phase 2 trial. Issue 7 (July 2019) - Long, Georgina V; Saw, Robyn P M; Lo, Serigne; Nieweg, Omgo E; Shannon, Kerwin F; Gonzalez, Maria; Guminski, Alexander; Lee, Jenny H; Lee, Hansol; Ferguson, Peter M; Rawson, Robert V; Wilmott, James S; et al.
Summary: Background: Adjuvant dabrafenib plus trametinib therapy improves relapse-free survival in patients with resected stage III melanoma. We aimed to ascertain the proportion of patients who would have a pathological response and a response according to Response Evaluation Criteria in Solid Tumors (RECIST) after neoadjuvant dabrafenib plus trametinib therapy for resectable clinical stage III melanoma. Methods: NeoCombi was a single-arm, open-label, single-centre, phase 2 study done at Melanoma Institute Australia (Sydney, NSW, Australia). Eligible patients were adults (aged ≥18 years) with histologically confirmed, resectable, RECIST-measurable, clinical stage IIIB–C (American Joint Committee on Cancer [AJCC] 7th edition), BRAF V600 -mutant melanoma, and had an Eastern Cooperative Oncology Group performance status of 1 or lower. Patients received 150 mg dabrafenib orally, twice daily, plus 2 mg trametinib orally, once daily, for 52 weeks (12 weeks of neoadjuvant therapy before complete resection of the pre-therapy tumour bed, and 40 weeks of adjuvant therapy thereafter). CT and PET scans were done at baseline and before resection. The primary outcomes were the proportion of patients achieving a complete pathological response and the proportion of patients achieving a response according to RECIST at week 12, analysed as per protocol. This trial is registered withClinicalTrials.gov, NCT01972347, and follow-up of patients is ongoing. Findings: Between Aug 20, 2014, and April 19, 2017, 40 patients were screened, of whom 35 eligible patients were enrolled, received neoadjuvant dabrafenib plus trametinib, and underwent resection. At the data cutoff (Sept 24, 2018), median follow-up was 27 months (IQR 21–36). At resection, 30 (86%) patients achieved a RECIST response; 16 (46%; 95% CI 29–63) had a complete response and 14 (40%; 24–58) had a partial response. Five patients (14%; 95% CI 5–30) had stable disease, and no patients progressed. After resection and pathological evaluation, all 35 patients achieved a pathological response, of whom 17 (49%; 95% CI 31–66) patients had a complete pathological response and 18 (51%; 95% CI 34–69) had a non-complete pathological response. Treatment-related serious adverse events occurred in six (17%) of 35 patients and grade 3–4 adverse events occurred in ten (29%) patients. No treatment-related deaths were reported. Interpretation: Neoadjuvant dabrafenib plus trametinib therapy could be considered in the management of RECIST-measurable resectable stage III melanoma as it led to a high proportion of patients achieving a complete response according to RECIST and a high proportion of patients achieving a complete pathological response, with no progression during neoadjuvant therapy. Funding: GlaxoSmithKline; Novartis; National Health and Medical Research Council, Australia; and Melanoma Institute Australia.